Enhancing Image Cryptography Performance with Block Left Rotation Operations - Al-Batah, Mohammad Subhi; Alzboon, Mowafaq Salem; Alzyoud, Mazen; Al-Shanableh, Najah (Applied Computational Intelligence and Soft Computing, 2024)
In today’s interconnected world, the transmission of both lengthy and concise text messages is ubiquitous across diverse communication platforms. With the proliferation of sensitive and specialized information being exchanged, safeguarding these messages from potential threats such as intruders, abusers, and data hackers becomes imperative. This study introduces an innovative approach aimed at streamlining data protection procedures while concurrently thwarting hacking attempts. At the core of this method lies the utilization of a sophisticated variable content private key designed to facilitate ease of alteration without compromising the integrity of encryption and decryption operations. The pivotal aspect involves leveraging a covert color image to generate this private key, mandating both the sender and receiver to securely retain this image. By employing a selected color image, the private key can seamlessly adapt to match the length of the confidential message. To fortify the level of security, the message is recommended to be segmented into blocks of predetermined sizes, with the sender and receiver jointly establishing these parameters. Subsequently, the bytes within each block are consolidated into a singular vector, which undergoes a left rotation by a predetermined number of bits as specified by the communicating parties. The proposed methodology is empirically validated through the implementation of various color images and text messages. Comparative analyses against existing methods underscore the efficacy and robustness of the proposed approach, substantiating its significant advancements in data protection paradigms.